(untitled) (Journal of Asian Development Studies, 2025)
This study investigates the perceptions and choices of the business community in Faisalabad regarding tree plantation, recognizing their potential as active contributors to urban sustainability. A descriptive research design was adopted. Five main roads in Faisalabad, i.e., Satyana Road, Jhang Road, Canal Road, Samundri Road, and Sargodha Road, were selected using a map grid method. Primary data were collected from business owners through structured questionnaires and face-to-face interviews. Perception was evaluated using four proxy variables, which were converted into a composite index and analyzed through multiple linear regression. Multinomial logistic regression was applied to assess choice behavior. Variables included enterprise size, owner’s gender, experience, income, education, ownership status, perceived benefits of trees, and awareness of tree management practices. Findings show that enterprise size, income, education level, gender, and business experience significantly influence perceptions about tree plantation. Additionally, choices regarding willingness to pay for plantation were affected by ownership status, perceived benefits, tree management concerns, and perceived importance of urban greenery. This study emphasizes that their decisions on tree species, irrigation, and plantation locations are not merely aesthetic but reflect adaptive behavior and resource constraints. Policy efforts must shift from top-down plantation drives to inclusive, enterprise sensitive, and localized urban greening strategies. Co-ownership and co-management of green infrastructure by commercial stakeholders could transform urban forestry into a scalable, economically integrated tool for climate resilience.